Efficacy and safety of oral hydroxyurea in transfusion-dependent β-thalassaemia: a protocol for randomised double-blind controlled clinical trial. Issue 10 (27th October 2020) - Yasara, Nirmani; Wickramarathne, Nethmi; Mettananda, Chamila; Manamperi, Aresha; Premawardhena, Anuja; Mettananda, Sachith
Abstract : Introduction: Despite being one of the first diseases to be genetically characterised, β-thalassaemia remains a disorder without a cure in a majority of patients. Most patients with β-thalassaemia receive only supportive treatment and therefore have a poor quality of life and shorter life spans. Hydroxyurea, which has shown to induce fetal haemoglobin synthesis in human erythroid cells, is currently recommended for the treatment of sickle cell disease. However, its clinical usefulness in transfusion-dependent β-thalassaemia is unclear. Here, we present a protocol for a randomised double-blind controlled clinical trial to evaluate the efficacy and safety of oral hydroxyurea in transfusion-dependent β-thalassaemia. Methods and analysis: This single-centre randomised double-blind placebo-controlled clinical trial is conducted at the Thalassaemia Centre of Colombo North Teaching Hospital, Ragama, Sri Lanka. Adult and adolescent patients with haematologically and genetically confirmed transfusion-dependent β-thalassaemia are enrolled and randomised into the intervention or control group. The intervention group receives oral hydroxyurea 10–20 mg/kg daily for 6 months, while the control group receives a placebo which is identical in size, shape and colour to hydroxyurea without its active ingredient. Transfused blood volume, pretransfusion haemoglobin level, fetal haemoglobin percentage and adverse effects of treatment are monitored during treatment and 6 months post-treatment. Cessation or reduction of blood transfusions during the treatment period will be the primary outcome measure. The statistical analysis will be based on intention to treat. Ethics and dissemination: Ethical approval has been obtained from the Ethics Committee of Faculty of Medicine, University of Kelaniya (P/116/05/2018) and the trial is approved by the National Medicinal Regulatory Authority of Sri Lanka. Results of the trial will be disseminated in scientific publications in reputed journals. Trial registration number: SLCTR/2018/024; Pre-results.